AN INTERACTIVE CHATBOT FOR PREDICTIVE DASHBOARD - Zulkifli, Nurzulaikha (IRC, 2020)
In the early days, customer service is always human. So, whenever user or customer faces any problem, they will always have to interact with customer service. However, human cannot always attend user and therefore user will have a hard time in trying to contact the service. So, with the current technology with AI driven will help to guide and solving user queries. Although this technology has been introduced since ‘60s, the usage of the system in every business application is still new. Chatbot can increase business revenues and attract user as it can produce data in real-time as well as available 24/7. Nuruzzaman, Mohammad and Hussain, Omar (2018) mentioned that there is demand in AI capabilities as it remove human issues and able to provide 24-hout services. Hence, business can run all times. Chatbot at occurrence can be an independent software but also can be integrated to dashboard. Dashboard and chatbot both have the same functions in which help business strategy in decision making. Dashboard is where the information is gathered with data visualizations to display and insight and predict historical data for future vision. Therefore, with the help of AI tools, company will be able to mov forward and able to move at par with technology.